The Present Status of Ugaritic Studies - Young, G. D.
1. Discovery and Publication of the Texts — 2. Translations and Studies on the Texts — 3. Ugarit's Contributions to: Biblical Research; Semitic Poetry; Literary Criticism; Archeology — 4. Phonology; Alphabet; Linguistic Affinities — 5. Lexicon — 6. Morphology and Syntax — 7. General Interpretation of the Literary Cycles.